Engineered extracellular vesicles efficiently deliver CRISPR-Cas9 ribonucleoprotein (RNP) to inhibit herpes simplex virus1 infection in vitro and in vivo - Yuanda Wan; Liren Li; Ruilin Chen; Jiajia Han; Qiyun Lei; Zhipeng Chen; Xiaodong Tang; Wenyu Wu; Shuwen Liu; Xingang Yao (Elsevier, 2024)
Extracellular vesicles (EVs) have recently emerged as a promising delivery platform for CRISPR/Cas9 ribonucleoproteins (RNPs), owing to their ability to minimize off-target effects and immune responses. However, enhancements are required to boost the efficiency and safety of Cas9 RNP enrichment within EVs. In response, we employed the Fc/Spa interaction system, in which the human Fc domain was fused to the intracellular domain of PTGFRN-Δ687 and anchored to the EV membrane. Simultaneously, the B domain of the Spa protein was fused to the C domain of cargos such as Cre or spCas9. Due to the robust interaction between Fc and Spa, this method enriched nearly twice the amount of cargo within the EVs. EVs loaded with spCas9 RNP targeting the HSV1 genome exhibited significant inhibition of viral replication in vitro and in vivo. Moreover, following neuron-targeting peptide RVG modification, the in vivo dosage in neural tissues substantially increased, contributing to the clearance of the HSV1 virus in neural tissues and exhibiting a lower off-target efficiency. These findings establish a robust platform for efficient EV-based SpCas9 delivery, offering potential therapeutic advantages for HSV1 infections and other neurological disorders.